Developing and Operationalizing a National Financial Inclusion Strategy : Toolkit - World Bank (World Bank, Washington, DC, 2018)
A national financial inclusion strategy (NFIS) can provide an effective instrument to chart a clear and coordinated path toward improving financial inclusion. An NFIS enables stakeholders to jointly define financial inclusion objectives, identify obstacles and opportunities relevant to the achievement of those objectives, and outline a prioritized set of actions to pursue in a coordinated manner. This toolkit provides financial sector authorities and other stakeholders with practical guidance on developing and operationalizing an NFIS. The toolkit covers three key areas: (i) the process of developing an NFIS, (ii) the key content of an NFIS document, and (iii) the operationalization of an NFIS. The toolkit includes detailed operational tips as well as country examples from over 20 countries. The toolkit is informed by the World Bank Group’s experience as a technical partner in the development and implementation of NFISs in a diverse range of country contexts.